2016
DOI: 10.1007/s12306-016-0408-1
|View full text |Cite
|
Sign up to set email alerts
|

Metallosis in shoulder arthroplasty: an integrative review of literature

Abstract: Shoulder arthroplasty has gained popularity as an efficient means of achieving pain relief and improved function in a variety of complex shoulder disorders. Despite promising reports, given the increasing number of shoulder arthroplasty procedures, various causes that may contribute to failure of a well-functioning arthroplasty are being increasingly recognized. One such disastrous condition is metallosis, a subject which has not been much talked off with reference to shoulder arthroplasty. This article beside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The treatment for metallosis is joint revision as chelating agents are not effective. 2 At her subsequent shoulder revision surgery, it was observed that approximately 40% of the glenoid base plate had been lost. Eight weeks postoperatively there was a noticeable reduction in the intensity of the pigmentation.…”
mentioning
confidence: 99%
“…The treatment for metallosis is joint revision as chelating agents are not effective. 2 At her subsequent shoulder revision surgery, it was observed that approximately 40% of the glenoid base plate had been lost. Eight weeks postoperatively there was a noticeable reduction in the intensity of the pigmentation.…”
mentioning
confidence: 99%
“…Total shoulder arthroplasty can fail for several reasons, such as component loosening, periprosthetic fracture, instability, infection, soft tissue failure, or joint overstuffing 5,13,16,17 . Metallosis‐induced conversion arthroplasty has been reported very rarely 3,4 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…4,15 Causative Factors of Revision Total shoulder arthroplasty can fail for several reasons, such as component loosening, periprosthetic fracture, instability, infection, soft tissue failure, or joint overstuffing. 5,13,16,17 Metallosis-induced conversion arthroplasty has been reported very rarely 3,4 (Table 1). During surgery, severe greenish metallic staining was found in the joint, confirming the diagnosis of metallosis, and diffuse wear was observed in the polyethylene insert.…”
Section: Metallosis and Revision To Reverse Total Shoulder Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…Plain radiographs have demonstrated poor sensitivity for identifying metallosis and radiographic signs are absent in over half of the cases. 11 Routine plain radiographs should be obtained to assess the glenohumeral joint space, implant positioning, and osteolysis suggestive of loosening and fracture. Characteristic CT findings of metallosis are high-density enhancement outlining the joint capsule or bursa.…”
Section: Discussionmentioning
confidence: 99%